ADÖLESANLARDA İNTERNET BAĞIMLILIĞI KAYGI VE SALDIRGAN DAVRANIŞLAR ARASINDAKİ İLİŞKİNİN BELİRLENMESİ. - Ayran, Gülsün (Karya Journal of Health Science, 2023)
Objective: This research was conducted to determine the relationship between internet addiction, anxiety and aggressive behaviors in adolescents. Method: This cross-sectional study was conducted between September and December 2022. A total of 336 students studying at a high school in eastern Turkey participated in the research. Data were collected with the “Questionniare Form”, “Young's Internet Addiction Test-Short Form”, “Buss-Perry Aggression Questionnaire” and “StateTrait Anxiety Inventory for Children”. Results: The mean age of the students in the study was 15.98±1.31 years, 59.8% of them were male and 30.1% of them were 10th grade students. It was determined that the students' Young's Internet Addiction Test-Short Form total score average was 24.51±9.72, the Buss-Perry Aggression Questionnaire total score average was 74.61±26.38, and the State-Trait Anxiety Inventory for Children total score average was 36.70±6.37. It was determined that there was a positive correlation between students' internet addiction level and aggression and anxiety levels, respectively (p<0.05). Conclusion: As a result, it was determined that the increase in the internet addiction scores of the students was associated with the increase in the aggression and anxiety scores.